Predesign of a Radial Inflow Turbine That Uses Supercritical Methane for a Mid-Scale Thruster for Upper Stage Application - Alexandru-Claudiu Cancescu; Daniel-Eugeniu Crunteanu; Anna-Maria Theodora Andreescu; Simona-Nicoleta Danescu (Aerospace)
The worldwide concern regarding the harmful effects of old polluting and toxic propellants has led to increased interest in new, green propellants and higher efficiency thrusters. This fact requires that a new generation of turbopumps, fit for these propellants, is developed. This paper focuses on the design of a radial inflow turbine, which was developed to power a single-shaft turbopump system for a 30 kN upper stage expander cycle thruster engine. The objective was to create a high-efficiency, compact, cheap-to-manufacture, 3D-printable turbine suitable to simultaneously power the methane and Oxygen pumps that feed the thruster. The total power consumed by the pumps for which this turbine was designed is 152 kW. The solution proposed in this paper includes measures such as elimination of the bladed diffuser, which was carried out to reduce the weight and the overall dimensions of the turbine. Comparing it with an axial turbine with the same power output, it has lower overall dimensions because it does not require a direction change at the inlet to the turbine bladed components, it does not require a stator to work, and its casing has a conical shape and is not cylindrical like the axial construction one. The proposed design has been analysed by CFD, which revealed that it can power the pumps. Analysis performed in off-design conditions indicated that the turbine has the best efficiency if the rotation speed and mass flow are varied at the same time. A breadboard model of the turbopump for which the turbine in this paper has been designed has been built using plastic and tested at pressures up to 6 bars using compressed air. The results indicate that above 1.5 bars of inlet pressure the turbine can overcome the internal resistances of the components and the rotor starts to spin. No indication of imbalance of the rotor was observed at maximum test pressure. Two configurations of the seals between the turbine and the adjacent pump have been tested, indicating that labyrinth seals must be doubled by floating ring seals.